THE RELATIONSHIP BETWEEN BREAST VOLUME AND BREAST MALIGNANCY IN MAMMOGRAPHY - Lathifa, Jauza Atsil; Yueniwati, Yuyun; Fahanani, Agwin Fahmi (International Journal of Radiology and Imaging, 2022)
Breast cancer is a major global public health problem and the most common type of cancer. The incidence of cases in Indonesia are about 42.1 per 100.000 population in 2019. There are multiple risk factors that underlie breast cancer malignancy. However, breast volume has not been yet included as a risk factor for breast cancer. The aim of this study is to analyze the association between breast volume and breast malignancy. This study is a cross-sectional study obtaining breast volume and BI-RADS score by performing mammography assessment at dr. Saiful Anwar General Hospital, Malang. The inclusion criteria were women aged > 40 years and excluded those who have mammography contraindications such as pregnancy and breast-feeding. The parameters for calculating breast volume were the width, height, and compression thickness, and the BI-RADS category (0 – 6) was used to determine the malignancy.   There is no significant association using the non-parametric analytic test Kruskal Wallis analytic test (p = 0.273 , p < 0.05) and a very weak negative correlation based on the correlation test Spearmanis correlation test (-0.127). There is no association between breast volume and the risk of malignancy based on BI-RADS mammography.